Cultural adaptation of an evidence-based home visitation programme: Latino clients' experiences of service delivery during implementation. Issue 4 (9th December 2014) - Finno-Velasquez, Megan; L. Fettes, Danielle; A. Aarons, Gregory; S. Hurlburt, Michael
Abstract : Purpose: – The purpose of this paper is to examine the experiences of Latino clients following a naturalistic cultural adaptation made to SafeCare, an evidence-based home visiting intervention designed to address specific linguistic and cultural issues affecting the Latino community during implementation in San Diego County, California. Design/methodology/approach: – Hierarchical linear models examined whether Latino clients experienced differences in perceptions of SafeCare delivery, working relationship with the home visitor and satisfaction with services when compared with non-Latino clients and whether language of service delivery and provider-client ethnic match were related to Latino clients' experiences of the intervention. Findings: – Overall, across several different dimensions, there was no decrement in experience with SafeCare for Latino clients compared to non-Latino ones, implying that adaptations made locally adequately engaged Latino and Spanish-speaking clients in services without compromising perceived adherence to the programme model. Research limitations/implications: – Because this was a non-experimental study, conclusions could not be drawn as to whether the locally adapted SafeCare would fare better in Latino client ratings than SafeCare unadapted. However, the findings are important because they contradict concerns that EBPs may not be relevant to diverse client groups, and support the idea that when adaptations are made, it is possible to maintain adherence at the same level of adherence as when the programme is delivered in its non-adapted form. Originality/value: – The study explicitly documents and generates knowledge around an organic adaptation made in a community to an evidence-based intervention for a client group about whom there has been documented concern regarding the relevance of and engagement in services.